Questions & Answers About Atrazine - Regehr, David L.; Peterson, Dallas E.; Hickman. John S. (My University, 1992)
This publication contains information about atrazine which is an herbicide that was commonly applied in Kansas.
MF1023_1992_02
Keywords: MF1023; Crops; Health and Safety; MF